2017
DOI: 10.2134/agronj2017.06.0309
|View full text |Cite
|
Sign up to set email alerts
|

Species‐Specific Contributions to Productivity and Weed Suppression in Cover Crop Mixtures

Abstract: Core Ideas Mustard, oat, sudangrass, and buckwheat were the most productive cover crops. Excluding mustard from spring mixtures sometimes increased weed biomass. Excluding sudangrass from summer mixtures sometimes increased weed biomass. Forage radish was less productive, but suppressed weeds in monoculture and mixture. Cover crops can provide many ecosystem services and on‐farm adoption is increasing. Cover crop mixtures are popular, but little is known about the functional contributions of individual species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Other studies have noted that higher seeding rates do not affect cover crop biomass, but are associated with lower winter weed biomass (Ryan et al, 2011), an effect attributed anecdotally to more ground cover. As the cover crops grown over the winter are directly competing with these winter weeds for resources like light, moisture, and soil nutrients, an indirect relationship between the two is expected and has been observed by other researchers (e.g., Dorn et al, 2015; Lawson et al, 2015; Holmes et al, 2017; Baraibar et al, 2018).…”
Section: Resultsmentioning
confidence: 63%
“…Other studies have noted that higher seeding rates do not affect cover crop biomass, but are associated with lower winter weed biomass (Ryan et al, 2011), an effect attributed anecdotally to more ground cover. As the cover crops grown over the winter are directly competing with these winter weeds for resources like light, moisture, and soil nutrients, an indirect relationship between the two is expected and has been observed by other researchers (e.g., Dorn et al, 2015; Lawson et al, 2015; Holmes et al, 2017; Baraibar et al, 2018).…”
Section: Resultsmentioning
confidence: 63%
“…Recent studies have not found strong relationships between the functional diversity of cover crop mixtures and enhanced weed suppression (Baraibar et al 2018;Holmes et al 2017;Smith et al 2015). In each study, cover crop species with traits that led to high resource acquisition (aboveground biomass, % ground cover) were weed suppressive in monoculture and tended to dominate cover crop mixtures.…”
Section: Which Cover Crop Response Traits Influence Erigeron Canadensmentioning
confidence: 88%
“…As a result of the wet and cool conditions following sowing in May, oat and ryegrass were more successful in limiting weed growth than sudangrass (Table 1). Holmes, Thompson, and Wortman (2017) studied the weed control potential of 12 different species used as cover crops planted at different sowing times (April vs. July). The authors reported that sudangrass was among the most effective at controlling weeds when sown in July.…”
Section: Weed Yieldmentioning
confidence: 99%